Arabic Scrambled Card Games for Vocabulary Mastery: An Experimental Study at The New College, Chennai - Dr K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study investigates the effectiveness of a modified card game, "Arabic Scrambled," on improving Arabic vocabulary (mufradat) mastery among undergraduate (UG) and postgraduate (PG) students in the Department of Arabic at The New College, Chennai. Arabic, classical language rich in literary nuance, is essential for Islamic studies but often presents learning challenges due to conventional teaching methods (Ibn Kathir, n.d.; Al-Khuli, 1982). Vocabulary acquisition is a critical yet often tedious component. This research employs a quantitative, one-group pretest-posttest design with 30 male students (15 UG, 15 PG) as respondents. The intervention used the "Arabic Scrambled" game, which requires players to assemble scrambled Arabic letters into words corresponding to images. Results from paired sample t-tests indicated a statistically significant improvement in post-test scores (p < 0.001), with a mean score increase from 37.63 to 69.75. The findings suggest that innovative, game-based learning tools like Arabic Scrambled can significantly enhance vocabulary retention, spelling accuracy, and comprehension, making Arabic language acquisition more engaging and effective in higher education settings.